Antimicrobial activity of a new class of synthetic retinoid antibiotics and comparator agents against ocular staphylococci - André, Camille; Schrank, Cassandra L.; Cheng Jaramillo, Ana Victoria; Mylonakis, Eleftherios; Wuest, William M.; Gilmore, Michael S.; Kim, Wooseong; Bispo, Paulo J. M. (Frontiers in Antibiotics, 2023)
Objectives: Antimicrobial resistance is global pandemic that poses a major threat to vision health as ocular pathogens, especially staphylococcal species, are becoming increasingly resistant to first-line therapies. Here we evaluated the antimicrobial activity of a new class of synthetic retinoids in comparison to currently used antibiotics against clinically relevant ocular staphylococcal isolates. Methods: Antimicrobial susceptibility testing was performed by broth microdilution for 3 novel synthetic retinoids (CD1530, CD437, and a CD437 analogue) and 7 comparator antibiotics, against a collection of 216 clinical isolates. Results: CD437 MIC50 and MIC90 were 2 µg/mL for Staphylococcus aureus, and 1 µg/mL and 2 µg/mL respectively, for coagulase-negative staphylococci (CoNS). CD1530 (MIC50 = 2 µg/mL for all species) also displayed good activity with an in vitro potency slightly lower (2-fold) for S. aureus (MIC90 = 4 µg/mL) when compared to CD437. A CD437 analogue also demonstrated good in vitro activity (MIC50 = 2 µg/mL for all species) and potency (MIC90 = 2 µg/mL for MRSA and 4 µg/mL for MSSA and CoNS). In vitro potencies were similar or higher than that of comparator agents, and were not impacted by multidrug resistance phenotypes. Conclusions: Our results demonstrate that synthetic retinoids display potent in vitro activity against ocular staphylococcal species, including multidrug-resistant isolates.